Coated steel sheets, components and their manufacturing methods
By introducing an appropriate amount of B elements into the steel plate and adopting a non-uniform dispersion of B, the shortcomings of existing high-strength steel plates in terms of delayed crack resistance and coating performance are solved, and the comprehensive effect of high strength, excellent delayed crack resistance and good coating performance is achieved.
Patent Information
- Application Number
- JP2024542001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-28
- Filing Date
- 2024-03-18
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2044-03-18
AI Technical Summary
The existing high-strength steel plates have shortcomings in terms of delayed crack resistance and coating properties, especially the delayed crack resistance is not fully considered.
By introducing B element into the steel plate, its content is controlled between 0.0008% and 0.0015%, and a non-uniform dispersion of B is used to form high and low concentrations of silicon and manganese oxides, enhancing the surface concentration of silicon and manganese oxides, and improving the resistance to delay cracks and coating properties.
The high strength of the steel plate (stress strength 1180 MPa or higher) and excellent delayed crack resistance and coating properties ensure the reliability and performance of the steel plate in use.
Smart Images

Figure 0007655454000001 
Figure 0007655454000002 
Figure 0007655454000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a plated steel sheet, a member, and a method for producing the same. [Background technology]
[0002] In addition to strength, automotive steel sheets must also have excellent resistance to delayed fracture. Patent Document 1 discloses a high-strength steel sheet with excellent workability and a manufacturing method thereof. Patent Document 2 discloses a high-strength cold-rolled steel sheet and a manufacturing method thereof. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2013-147736 A [Patent Document 2] JP 2008-106351 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the steel plates described in Patent Documents 1 and 2 both have a tensile strength TS of less than 1180 MPa, and delayed fracture resistance is not taken into consideration.
[0005] The present invention has been made in view of the above circumstances, and has an object to provide a plated steel sheet, a member, and a method for manufacturing the same, which have high strength with a tensile strength TS of 1,180 MPa or more and excellent delayed fracture resistance and plateability.
[0006] In the present invention, high strength means that the tensile strength TS measured in accordance with JIS Z2241 (2011) is 1180 MPa or more.
[0007] Moreover, "excellent resistance to delayed fracture" means that when a test piece is subjected to a constant load test with a tensile stress of 1800 MPa on the surface layer and immersed in a hydrochloric acid solution of pH 3 for 100 hours, no cracks are generated.
[0008] Moreover, "excellent plating ability" refers to the absence of unplated areas when visually inspected for the presence or absence of unplated areas. [Means for solving the problem]
[0009] Means for Solving the Problems The present inventors have conducted extensive research to achieve the above object, and as a result have obtained the following findings.
[0010] To obtain a tensile strength TS of 1180 MPa or more, it is recommended that martensite or bainite be the main phase. Also, it is effective to add 0.0015 mass% or more of B to improve delayed fracture resistance.
[0011] It is believed that B has the effect of strengthening the grain boundaries that serve as fracture paths by segregating to the prior austenite grain boundaries. On the other hand, when B is added, oxides of Si and Mn containing B are concentrated on the surface during annealing, which reduces galvanic properties. In this case, it was found that the effect on galvanic properties is small if the B content is less than 0.0015 mass%. Therefore, a method of improving delayed fracture resistance by setting the B content to less than 0.0015% was investigated. It was then conceived that by unevenly segregating B to the prior austenite grain boundaries, grain boundaries with high and low B concentrations could be created, and that even with a B content of less than 0.0015%, a sufficient amount of B could be segregated to some grain boundaries to improve delayed fracture resistance.
[0012] Therefore, we investigated a method to increase the B concentration at some grain boundaries by non-uniformly segregating B on the prior austenite grain boundaries. We found that B can be segregated non-uniformly by going through the process of B segregating on the grain boundaries twice and nucleating new austenite grains the second time. When cold-rolled sheet is annealed in the austenite region, B segregates at the austenite grain boundaries, but at this point, the diffusion of B is insufficient and solute B is present, so the segregated B is non-uniform but insufficiently concentrated. When this steel is cooled once to form martensite and bainite structures, and then annealed a second time, an austenite reverse transformation structure is formed. In this regard, if residual austenite exists after the first annealing and cooling, it will be used as a nucleus to form an austenite structure with the same crystal orientation as in the first annealing. Furthermore, martensite and bainite contain a large number of dislocations, and B that was dissolved in them will diffuse rapidly to the austenite grain boundaries through the dislocations during the second annealing, so that B will segregate uniformly. However, if it segregates uniformly, the grain boundary concentration of B will be low, so it is necessary to segregate B thickly only at some grain boundaries and thinly at other boundaries. Therefore, we focused on the fact that if sub-zero treatment is performed after the first annealing to remove some of the residual austenite, martensite with a high C concentration will be formed, and during the second annealing, austenite with a different crystal orientation from the austenite formed in the first annealing will newly nucleate from the martensite during the second annealing. The newly formed austenite grain boundaries are in different positions from the austenite grain boundaries formed in the first annealing, so the boron concentration is low and non-uniform. The retained austenite that transforms to martensite during sub-zero treatment is mainly blocky retained austenite, and film-like retained austenite remains even after sub-zero treatment. From these thin film-like retained austenite, austenite with the same crystal orientation as during the first annealing is formed. When this structure is cooled, ferrite is formed from the grain boundaries with low and non-uniform B concentration, and if the area ratio of ferrite is 3.0% or less, a high strength of 1180 MPa or more can be ensured. In the structure formed in this way, even if the B content is less than 0.0015%, B is concentrated at the prior austenite grain boundaries sandwiched on both sides by martensite, making it possible to improve delayed fracture resistance.
[0013] The present invention has been made based on the above findings. That is, the gist and configuration of the present invention are as follows. [1] In mass percent, C: 0.10% or more and 0.30% or less, Si: more than 1.20% and less than 2.00%, Mn: 2.5% or more and 4.0% or less, P: 0.050% or less, S: 0.020% or less, Al: 0.10% or less, N: 0.01% or less, Ti: 0.100% or less, Nb: 0.002% or more and 0.050% or less, and B: 0.0008% or more and less than 0.0015% and has a composition satisfying the following formula (1), with the balance being Fe and unavoidable impurities: The sum of the area ratios of martensite and bainite is 95.0% or more, The area ratio of retained austenite is 4.8% or less, The area ratio of ferrite is 0.2% or more and 3.0% or less, The prior austenite grain size is 10 μm or less, The B concentration of the prior austenite grain boundaries between adjacent martensites is 0.05% or more by mass%, The variation in B concentration within the same grain boundary of the prior austenite grain boundary between adjacent martensite grains is less than 0.010% by mass percent; A steel sheet in which the variation in B concentration within a prior austenite grain boundary present between martensite and ferrite is 0.010% or more by mass%, and a plating layer formed on at least one surface of the steel sheet. ([%N] / 14) / ([%Ti] / 47.9)<1.0...Equation (1) In formula (1), [%N] and [%Ti] respectively represent the N and Ti contents (mass%) in the steel. [2] The component composition further includes, in mass%, V: 0.100% or less, Mo: 0.500% or less Cr: 1.00% or less, Cu: 1.00% or less, Ni: 0.50% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.200% or less, W: 0.400% or less, Zr: 0.0200% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Co: 0.020% or less, REM: 0.0200% or less, Te: 0.020% or less, Hf: 0.10% or less, and Bi:0.200% or less The plated steel sheet according to the above [1], comprising at least one selected from the following: [3] A member made using the plated steel sheet according to [1] or [2] above. [4] A hot rolling process in which a steel slab having the composition described in [1] or [2] is hot rolled to form a hot rolled sheet; A pickling process for pickling the hot-rolled sheet; A cold rolling process in which the hot-rolled sheet after the pickling process is cold-rolled to obtain a cold-rolled sheet; A first annealing step of heating the cold-rolled sheet to a first heating temperature of Ac3 point or higher; A cooling process in which cooling is started from the first heating temperature to a cooling stop temperature of 100 ° C. or higher and lower than the Ms point at an average cooling rate of 50 ° C. / s or higher for the cold-rolled sheet after the first annealing process; After the cooling step, a reheating step of heating to a reheating temperature of 300° C. or more and 400° C. or less, holding the reheating temperature for 60 s or more, and cooling to room temperature; a sub-zero treatment step of performing sub-zero treatment after the reheating step; A second annealing step in which the steel sheet is obtained by heating the steel sheet to a second heating temperature of Ac3 or higher after the sub-zero treatment step; and a plating step of subjecting the steel sheet to a plating treatment to obtain a plated steel sheet. [5] A method for producing a plated steel sheet according to [4] above, comprising, after the plating step, an alloying step of subjecting the plated steel sheet to an alloying treatment. [6] A method for manufacturing a component, comprising the step of subjecting the plated steel sheet according to [1] or [2] above to at least one of forming and joining to form a component. Effect of the Invention
[0014] According to the present invention, it is possible to provide a plated steel sheet, a member, and a method for producing the same, which have a high strength with a tensile strength TS of 1180 MPa or more and excellent delayed fracture resistance and plateability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0016] The plated steel sheet according to the present embodiment contains, by mass%, C: 0.10% or more and 0.30% or less, Si: more than 1.20% and 2.00% or less, Mn: 2.5% or more and 4.0% or less, P: 0.050% or less, S: 0.020% or less, Al: 0.10% or less, N: 0.01% or less, Ti: 0.100% or less, Nb: 0.002% or more and 0.050% or less, and B: 0.0008% or more and less than 0.0015%, and satisfies the following formula (1), with the balance being Fe and unavoidable impurities. The total area ratio of martensite and bainite is 95.0% or more, and the area ratio of retained austenite is 4.0% or more. The steel sheet has a boron concentration of 0.05% or more by mass, a ferrite area ratio of 0.2% to 3.0%, a prior austenite grain size of 10 μm or less, a prior austenite grain boundary between adjacent martensite particles having a boron concentration of 0.05% or more by mass, a variation in the boron concentration of the prior austenite grain boundary between adjacent martensite particles within the same grain boundary of less than 0.010% by mass, and a plating layer formed on at least one surface of the steel sheet. ([%N] / 14) / ([%Ti] / 47.9)<1.0...Equation (1) In formula (1), [%N] and [%Ti] respectively represent the N and Ti contents (mass%) in the steel.
[0017] [Component composition] First, the appropriate range of the composition of the steel sheet and the reason for limiting it will be described. In the following description, "%" representing the content of the component elements of the steel sheet means "% by mass" unless otherwise specified. "ppm" means "ppm by mass" unless otherwise specified. In this specification, a numerical range expressed using "to" means a range including the numerical values written before and after "to" as the lower and upper limits.
[0018] C: 0.10% or more and 0.30% or less C has the effect of strengthening the martensite-bainite structure. If the C content is less than 0.10%, the area ratio of martensite and bainite decreases, and a tensile strength TS (hereinafter sometimes simply referred to as TS) of 1180 MPa or more cannot be obtained. Therefore, the C content is set to 0.10% or more. The C content is preferably set to 0.11% or more. On the other hand, if the C content exceeds 0.30%, a carboboride of B and iron is formed during annealing, and a sufficient amount of B cannot be segregated on the grain boundaries. Therefore, the C content is set to 0.30% or less. The C content is preferably 0.28% or less.
[0019] Si: more than 1.20% and less than 2.00% Silicon is an effective element for solid solution strengthening, and also has the effect of suppressing the precipitation of carboborides that deteriorate the delayed fracture resistance, so a content of more than 1.20% is required. If the content is 1.20% or less, carboborides precipitate, the B concentration at the grain boundaries decreases, and the delayed fracture resistance decreases. Therefore, the Si content is set to more than 1.20%. The Si content is preferably set to 1.30% or more. On the other hand, since Si is a ferrite stabilizing element and raises the transformation point, if the Si content exceeds 2.00%, the annealing temperature becomes too high and the prior austenite grain size cannot be made 10 μm or less. Therefore, the Si content is set to 2.00% or less. The Si content is preferably set to 1.80% or less.
[0020] Mn: 2.5% or more and 4.0% or less Mn is effective in improving hardenability. If the Mn content is less than 2.5%, the area ratio of martensite and bainite decreases, resulting in a decrease in strength. Therefore, the Mn content is set to 2.5% or more. The Mn content is preferably set to 2.8% or more. On the other hand, if the Mn content exceeds 4.0%, the segregated portion becomes excessively hard and the delayed fracture resistance property is deteriorated. Therefore, the Mn content is set to 4.0% or less, and preferably, the Mn content is set to 3.5% or less.
[0021] P:0.050% or less Since P segregates at prior austenite grain boundaries and reduces delayed fracture resistance, the P content is set to 0.050% or less. The P content is preferably set to 0.025% or less. There is no particular lower limit for the P content, and it may be 0%, but since a content of less than 0.001% increases manufacturing costs, a content of 0.001% or more is preferable.
[0022] S: 0.020% or less Since S segregates at prior austenite grain boundaries and reduces delayed fracture resistance, the S content is set to 0.020% or less. The S content is preferably set to 0.018% or less. The S content is more preferably set to 0.0040% or less, and further preferably set to 0.0020% or less. There is no particular lower limit for the S content, but since a content of less than 0.0001% increases the production costs, it is preferable to set the S content to 0.0001% or more.
[0023] Al: 0.10% or less Al is an element that acts as a deoxidizer, and in order to obtain such an effect, the Al content is preferably 0.005% or more. On the other hand, if the Al content exceeds 0.10%, ferrite is easily generated and the strength decreases. Therefore, the Al content is set to 0.10% or less. The Al content is preferably set to 0.05% or less.
[0024] N: 0.01% or less N forms nitrides with Nb and B, reducing the effects of adding Nb and B. Therefore, the N content is set to 0.01% or less. The N content is preferably set to 0.006% or less. There is no particular lower limit, but from the viewpoint of manufacturing costs, the N content is preferably set to 0.0001% or more.
[0025] Ti:0.100% or less Ti has the effect of fixing N in steel as TiN, suppressing the formation of BN and NbN, improving the effect of adding Nb and B, and improving delayed fracture resistance. In order to obtain these effects, the Ti content is preferably 0.005% or more. On the other hand, if the Ti content exceeds 0.100%, coarse Ti carbides are formed on the grain boundaries, and the delayed fracture resistance is reduced. Therefore, the Ti content is set to 0.100% or less. The Ti content is preferably set to 0.050% or less.
[0026] Nb: 0.002% or more and 0.050% or less Nb precipitates as a solid solution or fine carbides, and inhibits the growth of austenite grains during annealing. It also refines the grain size, complicates the fracture path, and improves delayed fracture resistance. To obtain such effects, the Nb content is set to 0.002% or more. The Nb content is preferably set to 0.005% or more. On the other hand, if the Nb content exceeds 0.050%, not only does the effect saturate, but also coarse Nb carbides precipitate, deteriorating the delayed fracture resistance. Therefore, the Nb content is set to 0.050% or less. Moreover, the Nb content is preferably set to 0.040% or less.
[0027] B: 0.0008% or more and less than 0.0015% B has the effect of segregating at prior austenite grain boundaries to increase grain boundary strength and improve delayed fracture resistance. To obtain such an effect, the B content is set to 0.0008% or more. The B content is preferably set to 0.0009% or more. On the other hand, if the B content is 0.0015% or more, it will concentrate on the steel sheet surface together with Si and Mn during annealing to form oxides, which will deteriorate the surface appearance and galvanic properties. In addition, carboborides will form, which will deteriorate the delayed fracture resistance. Therefore, the B content is set to less than 0.0015%. The B content is preferably set to 0.0014% or less.
[0028] ([%N] / 14) / ([%Ti] / 47.9)<1.0...Equation (1) In order to obtain the above-mentioned effects of adding B and Nb, N, which easily bonds with these elements, needs to be fixed by Ti. For this purpose, the molar fraction of N is made smaller than the molar fraction of Ti. In other words, the contents of N and Ti in the steel are adjusted so as to satisfy the above formula (1). ([%N] / 14) / ([%Ti] / 47.9) is preferably 0.6 or less. In the formula (1), [%N] and [%Ti] respectively represent the N and Ti contents (mass%) in the steel.
[0029] The balance other than the above-mentioned components is Fe and inevitable impurities. Note that, for the optional components described below, if the content is less than the lower limit, the effect of the present invention is not impaired, so if these optional elements are contained in an amount less than the lower limit, they are treated as inevitable impurities.
[0030] [Optional ingredients] In addition to the above-mentioned chemical composition, the steel sheet of the plated steel sheet according to this embodiment may further contain, by mass%, at least one element selected from V: 0.100% or less, Mo: 0.500% or less, Cr: 1.00% or less, Cu: 1.00% or less, Ni: 0.50% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.200% or less, W: 0.400% or less, Zr: 0.0200% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Co: 0.020% or less, REM: 0.0200% or less, Te: 0.020% or less, Hf: 0.10% or less, and Bi: 0.200% or less.
[0031] V:0.100% or less V has the effect of forming fine carbides and increasing strength. If the V content exceeds 0.100%, coarse V carbides are precipitated, and the delayed fracture resistance may decrease. Therefore, when V is contained, the V content is set to 0.100% or less. The V content is preferably 0.080% or less, and more preferably 0.060% or less. The lower limit of the V content is not particularly limited and may be 0.000%, but since V has the effect of forming fine carbides and increasing strength, it is preferably 0.001% or more, more preferably 0.005% or more, and further preferably 0.010% or more.
[0032] Mo: 0.500% or less Mo has the effect of improving hardenability and increasing the area ratio of bainite and martensite. If the Mo content exceeds 0.500%, the effect is saturated. Therefore, if Mo is contained, the Mo content is set to 0.500% or less. The Mo content is preferably 0.200% or less, and more preferably 0.150% or less. The lower limit of the Mo content is not particularly limited and may be 0.000%, but since Mo has the effect of improving hardenability and increasing the area ratio of bainite and martensite, it is preferably 0.010% or more, more preferably 0.020% or more, and further preferably 0.030% or more.
[0033] Cr:1.00% or less Cr has the effect of improving hardenability and increasing the area ratio of bainite and martensite. If the Cr content exceeds 1.00%, the effect is saturated. Therefore, if Cr is contained, the Cr content is set to 1.00% or less. The Cr content is preferably 0.300% or less, and more preferably 0.250% or less. The lower limit of the Cr content is not particularly limited and may be 0.000%, but is preferably 0.01% or more because it has the effect of improving hardenability and increasing the area ratio of bainite and martensite. The Cr content is more preferably 0.015% or more, and further preferably 0.030% or more.
[0034] Cu: 1.00% or less Cu has the effect of increasing strength by solid solution. Cu also has the effect of improving delayed fracture resistance. If the Cu content exceeds 1.00%, grain boundary cracking is likely to occur. Therefore, when Cu is contained, the Cu content is set to 1.00% or less. The Cu content is preferably 0.60% or less, and more preferably 0.30% or less. The lower limit of the Cu content is not particularly limited and may be 0.00%, but since it has the effect of increasing strength by solid solution, it is preferably 0.01% or more, more preferably 0.02% or more, and further preferably 0.05% or more.
[0035] Ni: 0.50% or less Ni has the effect of improving hardenability, but if the Ni content exceeds 0.50%, the effect is saturated. Therefore, when Ni is contained, the Ni content is set to 0.50% or less. The Ni content is preferably 0.20% or less, and more preferably 0.15% or less. The lower limit of the Ni content is not particularly limited and may be 0.00%, but since Ni has an effect of improving hardenability, it is preferably 0.01% or more, more preferably 0.02% or more, and further preferably 0.03% or more.
[0036] Sb: 0.200% or less Sb has the effect of suppressing the surface oxidation, nitridation, and decarburization of the steel sheet, but if the Sb content exceeds 0.200%, the effect is saturated. Therefore, if Sb is contained, the Sb content is set to 0.200% or less. The Sb content is preferably 0.050% or less, and more preferably 0.020% or less. The lower limit of the Sb content is not particularly limited and may be 0.000%, but since Sb has the effect of suppressing the surface oxidation, nitridation, and decarburization of the steel sheet, it is preferably 0.001% or more. The Sb content is more preferably 0.002% or more, and further preferably 0.005% or more.
[0037] Sn: 0.200% or less Like Sb, Sn has the effect of suppressing the surface oxidation, nitridation, and decarburization of the steel sheet. If the Sn content exceeds 0.200%, the effect is saturated. Therefore, if Sn is contained, the Sn content is set to 0.200% or less. The Sn content is preferably 0.050% or less, and more preferably 0.020% or less. The lower limit of the Sn content is not particularly limited and may be 0.000%, but since it has the effect of suppressing surface oxidation, nitridation, and decarburization of the steel sheet, it is preferably 0.001% or more. The Sn content is more preferably 0.002% or more, and further preferably 0.005% or more.
[0038] Ta: 0.200% or less Ta has the effect of forming fine carbides and increasing strength. If the Ta content exceeds 0.200%, coarse Ta carbides are precipitated, and the delayed fracture resistance may decrease. Therefore, if Ta is contained, the Ta content is set to 0.200% or less. The Ta content is preferably 0.100% or less, and more preferably 0.070% or less. The lower limit of the Ta content is not particularly limited and may be 0.000%, but since it has the effect of forming fine carbides and increasing strength, it is preferably 0.001% or more. The Ta content is more preferably 0.005% or more, and further preferably 0.010% or more.
[0039] W:0.400% or less W has the effect of forming fine carbides and increasing strength. If the W content exceeds 0.400%, coarse W carbides are precipitated, and the delayed fracture resistance may decrease. Therefore, when W is contained, the W content is set to 0.400% or less. The W content is preferably 0.300% or less, and more preferably 0.250% or less. The lower limit of the W content is not particularly limited and may be 0.000%, but since it has the effect of forming fine carbides and increasing strength, it is preferably 0.001% or more. The W content is more preferably 0.005% or more, and further preferably 0.010% or more.
[0040] Zr: 0.0200% or less Zr has the effect of improving toughness by making the shape of inclusions spherical and suppressing stress concentration. If the Zr content exceeds 0.0200%, a large amount of inclusions may be formed, and the toughness may decrease. Therefore, if Zr is contained, the Zr content is set to 0.0200% or less. The Zr content is preferably 0.0150% or less, and more preferably 0.0100% or less. The lower limit of the Zr content is not particularly limited and may be 0.0000%, but since it has the effect of making the shape of inclusions spherical, suppressing stress concentration, and improving toughness, it is preferably 0.0001% or more. The Zr content is more preferably 0.0010% or more, and further preferably 0.0020% or more.
[0041] Ca:0.0200% or less Ca can be used as a deoxidizer. If the Ca content exceeds 0.0200%, a large amount of Ca-based inclusions are generated, and the delayed fracture resistance may deteriorate. Therefore, if Ca is contained, the Ca content is set to 0.0200% or less. The Ca content is preferably 0.0100% or less, and more preferably 0.0080% or less. The lower limit of the Ca content is not particularly limited and may be 0.0000%, but since it can be used as a deoxidizer, it is preferably 0.0001% or more. The Ca content is more preferably 0.0005% or more, and further preferably 0.0010% or more.
[0042] Mg: 0.0200% or less Mg can be used as a deoxidizer. If the Mg content exceeds 0.0200%, a large amount of Mg-based inclusions are generated, and the delayed fracture resistance may deteriorate. Therefore, if Mg is contained, the Mg content is set to 0.0200% or less. The Mg content is preferably 0.0100% or less, and more preferably 0.0080% or less. The lower limit of the Mg content is not particularly limited and may be 0.0000%, but since it can be used as a deoxidizer, it is preferably 0.0001% or more, more preferably 0.0005% or more, and further preferably 0.0010% or more.
[0043] Co:0.020% or less Co has the effect of increasing strength by solid solution strengthening. If the Co content exceeds 0.020%, the effect is saturated. Therefore, if Co is contained, the Co content is set to 0.020% or less. The Co content is preferably 0.015% or less, and more preferably 0.010% or less. The lower limit of the Co content is not particularly limited and may be 0.000%, but since Co has the effect of increasing strength by solid solution strengthening, it is preferably 0.001% or more. The Co content is more preferably 0.002% or more, and further preferably 0.005% or more.
[0044] REM: 0.0200% or less REM has the effect of improving toughness by making the shape of inclusions spherical and suppressing stress concentration. If the REM content exceeds 0.0200%, a large amount of inclusions may be formed, which may reduce toughness. Therefore, if REM is contained, the REM content is set to 0.0200% or less. The REM content is preferably 0.0100% or less, and more preferably 0.0050% or less. The lower limit of the REM content is not particularly limited and may be 0.0000%, but since it has the effect of making the shape of inclusions spherical, suppressing stress concentration, and improving toughness, it is preferably 0.0001% or more. The REM content is more preferably 0.0005% or more, and further preferably 0.0010% or more. Here, REM refers to scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoid elements with atomic numbers from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The REM concentration is the total content of one or more elements selected from the above REM. As the REM, it is preferable to have La, Ce, and Nd.
[0045] Te: 0.020% or less Te has the effect of improving toughness by making the shape of inclusions spherical and suppressing stress concentration. If the Te content exceeds 0.020%, a large amount of inclusions may be formed, and the toughness may decrease. Therefore, if Te is contained, the Te content is set to 0.020% or less. The Te content is preferably 0.015% or less, and more preferably 0.010% or less. The lower limit of the Te content is not particularly limited and may be 0.000%, but since it has the effect of making the shape of inclusions spherical, suppressing stress concentration, and improving toughness, it is preferable to make it 0.001% or more. The Te content is more preferably 0.002% or more, and further preferably 0.004% or more.
[0046] Hf: 0.10% or less Hf has the effect of improving toughness by making the shape of inclusions spherical and suppressing stress concentration. If the Hf content exceeds 0.10%, a large amount of inclusions is formed and the toughness decreases. Therefore, if Hf is contained, the Hf content is set to 0.10% or less. The Hf content is preferably 0.08% or less, and more preferably 0.05% or less. The lower limit of the Hf content is not particularly limited and may be 0.00%, but it is preferable to set it to 0.01% or more since Hf has the effect of making the shape of inclusions spherical, suppressing stress concentration, and improving toughness.
[0047] Bi:0.200% or less Bi has the effect of reducing segregation and improving bendability. If the Bi content exceeds 0.200%, a large amount of inclusions may be formed, resulting in a decrease in bendability. Therefore, when Bi is contained, the Bi content is set to 0.200% or less. The Bi content is preferably 0.100% or less, and more preferably 0.050% or less. The Bi content is further preferably 0.010% or less, and even more preferably 0.005% or less. The lower limit of the Bi content is not particularly limited and may be 0.000%, but since Bi has the effect of reducing segregation and improving bendability, it is preferably 0.001% or more, more preferably 0.002% or more, and further preferably 0.003% or more.
[0048] [Steel structure] Next, the steel structure of the steel plate will be described.
[0049] Total area ratio of martensite and bainite: 95.0% or more Both martensite and bainite are hard phases and are necessary to achieve a TS of 1180 MPa or more. Therefore, the total area ratio of martensite and bainite is 95.0% or more. The total area ratio of martensite and bainite is preferably 96.0% or more. Since ferrite is generated from grain boundaries with non-uniform B concentration, the upper limit of the total area ratio of martensite and bainite is 99.8%.
[0050] Area ratio of retained austenite: 4.8% or less The retained austenite may be contained as a residual structure other than martensite and bainite. Therefore, the area ratio of the retained austenite is 4.8% or less. More preferably, it is 4.7% or less, and even more preferably, it is 4.5% or less. Also, the area ratio of the retained austenite is preferably 4% or less. More preferably, it is 3.8% or less, and even more preferably, it is 3.7% or less, and even more preferably, it is 3.5% or less. The area ratio of the retained austenite may be 0% or more than 0%.
[0051] Ferrite area ratio: 0.2% to 3.0% Ferrite is formed from austenite grain boundaries with non-uniform B concentration. If the area ratio of ferrite is 0.2% or more, the B concentration of the prior austenite grain boundaries where ferrite is not formed is sufficiently high, and the delayed fracture resistance is good. Therefore, the area ratio of ferrite is set to 0.2% or more. The area ratio of ferrite is preferably set to 0.3% or more, and more preferably set to 0.5% or more. On the other hand, if the area ratio of ferrite exceeds 3.0%, the strength decreases. Therefore, the area ratio of ferrite is set to 3% or less. The area ratio of ferrite is preferably set to 2.5% or less, and more preferably set to 2.0% or less.
[0052] Here, the area ratio of each structure is measured as follows. The area ratio of retained austenite is determined by chemically polishing the rolled surface of a test piece taken from each steel plate up to the t / 4 position of the steel plate thickness, measuring the X-ray diffraction intensity and diffraction peak position of the polished surface with an X-ray diffraction device (X-ray diffraction: XRD) to calculate the volume ratio, and this number is the area ratio of retained austenite. Next, the plate thickness cross section parallel to the rolling direction of each steel plate is polished and etched with 3 vol% nital, and the plate thickness t / 4 position is used as the observation surface. SEM images of the observation surface are taken at a magnification of 2000 times with a field of view of 57.1 μm × 42.9 μm in three fields of view. The obtained SEM images are analyzed to determine the total area ratio of martensite, bainite, and retained austenite, as well as the area ratio of structures other than martensite, bainite, and retained austenite (ferrite). The area ratios of martensite and bainite are calculated by subtracting the area ratio of retained austenite obtained by XRD from the area ratios of martensite, bainite, and retained austenite obtained by image analysis. The average value of the three fields of view is taken as the area ratio of the structure.
[0053] Prior austenite grain size: 10μm or less By making the crack propagation path more complex, it is possible to improve delayed fracture resistance. To achieve this effect, the prior austenite grain size must be 10 μm or less. Therefore, the prior austenite grain size is set to 10 μm or less. The prior austenite grain size is preferably 9 μm or less. There is no particular lower limit to the grain size of the prior austenite grains, but from the viewpoint of production technology, the prior austenite grain size is preferably 1 μm or more. Moreover, the prior austenite grain size is more preferably 2 μm or more, and even more preferably 3 μm or more.
[0054] Here, the grain size of the prior austenite grains is measured as follows. A cross-section of each steel plate parallel to the rolling direction is polished and then etched with picral to provide an observation surface. On the observation surface, the microstructure at the position of t / 4 of the plate thickness is photographed with an SEM at a magnification of 2000 times and a field of view of 57.1 μm × 42.9 μm, and three fields of view are photographed to obtain SEM images. The grain size of each prior austenite grain is determined from the obtained structural image by image analysis, and the average value of the three fields of view is taken as the grain size of the prior austenite grains (average crystal grain size).
[0055] B concentration at prior austenite grain boundaries between adjacent martensite: 0.05% or more by mass B segregates at the prior austenite grain boundaries to strengthen the grain boundaries and improve delayed fracture resistance. If the B concentration at the prior austenite grain boundaries is 0.05% or more by mass, the above effect can be obtained. Therefore, the B concentration at the prior austenite grain boundaries between adjacent martensites (prior austenite grain boundaries sandwiched between martensite structures) is set to 0.05% or more by mass. The B concentration at the prior austenite grain boundaries is preferably 0.07% or more by mass, and more preferably 0.10% or more by mass. Although there is no upper limit for the B concentration in the prior austenite grain boundaries, in order to suitably prevent the precipitation of hard carboborides on the grain boundaries and further improve the delayed fracture resistance, the B concentration is preferably less than 6%, and more preferably 2% or less by mass.
[0056] Variation in B concentration within the same grain boundary of prior austenite grains between adjacent martensite: Less than 0.010% by mass In order to improve delayed fracture resistance, in addition to the B concentration on the grain boundaries, it is also important that the concentration is uniform regardless of the grain boundaries. If the variation is 0.010% or more, strength differences will occur within the grain boundaries, making cracks more likely to occur in areas with locally low B concentration, and the effect of improving delayed fracture will be reduced. Therefore, the variation in the B concentration within the same grain boundary of the prior austenite grain boundary (prior austenite grain boundary sandwiched on both sides by martensite structure) existing between adjacent martensite structures is set to less than 0.010% by mass. The variation is preferably 0.009% or less by mass, and more preferably 0.008% or less by mass. Although the smaller the variation, the better, from the viewpoint of production technology, the variation should be 0.001% or more. Also, the grain boundary where B segregation contributes to improving delayed fracture resistance is a grain boundary where both sides are martensite.
[0057] Variation in B concentration within the same grain boundary of prior austenite grain boundaries between martensite and ferrite: 0.010% or more by mass By forming a grain boundary between martensite and ferrite, the B concentration of the prior austenite grain boundary sandwiched between martensite on both sides can be set to 0.05% by mass or more. If the variation in the B concentration of the prior austenite grain boundary between martensite and ferrite within the same grain boundary is less than 0.010%, ferrite will not be formed. Therefore, the variation in the B concentration of the prior austenite grain boundary (prior austenite grain boundary sandwiched between martensite structure and ferrite) within the same grain boundary between martensite and ferrite is set to 0.010% by mass or more. The variation is preferably 0.012% by mass or more, more preferably 0.014% by mass or more. The upper limit is not particularly limited, but the variation is preferably 0.200% or less in mass %, and more preferably 0.100% or less in mass %.
[0058] Here, the B concentration and variation of the prior austenite grain boundary are measured as follows. A needle-shaped sample is prepared from a region including the prior austenite grain boundary by the SEM-FIB (Focused Ion Beam) method. The obtained needle-shaped sample is subjected to 3DAP analysis using a 3DAP device (LEAP4000XSi, manufactured by AMETEK). The measurement is performed in laser mode. The sample temperature is 80K or less. The B concentration of the prior austenite grain boundary is obtained from the number of B ions and the number of other ions detected from the prior austenite grain boundary. The B concentration is the average value of the two samples. In addition, five non-overlapping circular regions with a diameter of 5 nm to 10 nm are set on the surface of the measured prior austenite grain boundary, and a cylindrical volume extending in the normal direction of the grain boundary is set for each circle. The B concentration on the grain boundary is obtained for each cylinder, and the standard deviation is taken as the variation in the B concentration. In the above measurements, the prior austenite grain size is much larger than the area sampled by the SEM-FIB method, so the grain boundaries targeted by one sampled sample are all the same grain boundaries. For example, the prior austenite grain size is about 9 μm, while the sampled sample area is about 0.1 μm in diameter. Therefore, the variation in the obtained B concentration is the variation within the same grain boundary. In addition, whether or not a prior austenite grain boundary exists between martensite and ferrite can be confirmed by observing the SEM image by the above-mentioned method, and whether or not a prior austenite grain boundary exists between adjacent martensite can also be confirmed by observing the SEM image by the above-mentioned method.
[0059] According to the present invention, it is possible to provide a plated steel sheet having a tensile strength of 1180 MPa or more. The tensile strength of the plated steel sheet is preferably 1250 MPa or more.
[0060] The above-mentioned plated steel sheet has a plating layer formed on at least one side of the steel sheet. The plating layer is preferably any one of a hot-dip galvanized layer, a galvannealed hot-dip galvanized layer, and an electrolytic galvanized layer. The composition of the plating layer is not particularly limited and may be a known composition.
[0061] The composition of the hot-dip galvanized layer is not particularly limited and may be any common one. In one example, the coating layer contains Fe: 20 mass% or less, Al: 0.001 mass% to 1.0 mass% or less, and further contains one or more selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0 mass% to 3.5 mass%, with the remainder being Zn and unavoidable impurities. When the plating layer is a hot-dip galvanized layer, in one example, the Fe content in the plating layer is less than 7 mass%, and when the plating layer is an alloyed hot-dip galvanized layer, in one example, the Fe content in the plating layer is 7 mass% or more and 15 mass% or less, more preferably 8 mass% or more and 13 mass% or less.
[0062] The coating weight is not particularly limited, but the coating weight per one side of the plated steel sheet is preferably 20 to 80 g / m 2 In one example, the plating layer is formed on both the front and back surfaces of a steel sheet (high-strength cold-rolled steel sheet).
[0063] Next, a method for producing a plated steel sheet will be described. The method for producing a plated steel sheet according to this embodiment includes a hot rolling process in which a steel slab having the above-mentioned composition is hot-rolled to obtain a hot-rolled sheet, a pickling process in which the hot-rolled sheet is pickled, a cold rolling process in which the hot-rolled sheet after the pickling process is cold-rolled to obtain a cold-rolled sheet, a first annealing process in which the cold-rolled sheet is heated to a first heating temperature of Ac3 point or higher, a cooling process in which cooling of the cold-rolled sheet after the first annealing process is started from the first heating temperature and cooled to a cooling stop temperature of 100°C or higher and lower than the Ms point at an average cooling rate of 50°C / s or higher, a reheating process in which, after the cooling process, the cold-rolled sheet is heated to a reheating temperature of 300°C or higher and 400°C or lower, and held at the reheating temperature for 60s or more and cooled to room temperature, a subzero treatment process in which, after the reheating process, a subzero treatment process is performed, a second annealing process in which, after the subzero treatment process, a steel sheet is obtained by heating to a second heating temperature of Ac3 point or higher, and a plating process in which the steel sheet is plated to obtain a plated steel sheet.
[0064] First, a steel slab having the above-mentioned composition is produced. Here, an example of manufacturing conditions for a steel slab before the hot rolling process will be described. First, the steel material is melted to obtain molten steel having the above-mentioned composition. The melting method is not particularly limited, and any of the known melting methods such as converter melting and electric furnace melting are suitable. The obtained molten steel is solidified to produce a steel slab. The method for producing a steel slab from molten steel is not particularly limited, and a continuous casting method, an ingot casting method, a thin slab casting method, or the like can be used. The steel slab may be cooled once and then reheated before being subjected to hot rolling, or the cast steel slab may be continuously hot rolled without being cooled to room temperature. The slab heating temperature is preferably 1100°C or higher, and 1300°C or lower, taking into consideration the rolling load and the generation of scale. The slab heating method is not particularly limited, and for example, it can be heated in a heating furnace according to a conventional method.
[0065] [Hot rolling process] The above-mentioned steel slab is hot-rolled to obtain a hot-rolled sheet. There is no particular restriction on the hot rolling, and it may be performed according to a conventional method. There is also no particular restriction on the cooling after hot rolling, and it is cooled to the coiling temperature. Next, the hot-rolled sheet is wound into a coil. The coiling temperature is preferably 400°C or higher. If the coiling temperature is 400°C or higher, the strength of the hot-rolled sheet does not increase and the coiling becomes easy. The coiling temperature is more preferably 550°C or higher. In addition, in order to suitably prevent the scale from being formed thickly and to further improve the yield, the coiling temperature is preferably 750°C or lower. Note that the hot-rolled sheet may be heat-treated for the purpose of softening before pickling.
[0066] [Pickling process] After the hot rolling process, the hot-rolled sheet is pickled in a pickling process. In the pickling process, the scale of the hot-rolled sheet wound around the coil can be removed. The method for removing the scale is not particularly limited, but in order to completely remove the scale, it is preferable to perform pickling while uncoiling the hot-rolled coil. The pickling method is not particularly limited, and may be a conventional method.
[0067] [Cold rolling process] After the pickling process, the hot-rolled sheet is subjected to cold rolling in a cold rolling process to obtain a cold-rolled sheet. For example, the hot-rolled sheet from which the scale has been removed is appropriately washed and then cold-rolled to obtain a cold-rolled sheet. The method of cold rolling is not particularly limited and may be a conventional method.
[0068] [First annealing process: Heat to the first heating temperature of Ac3 or higher] Next, in the first annealing step, the cold-rolled sheet is heated to a first heating temperature of the Ac3 point or higher and annealed in the austenite single phase region. If the first heating temperature is lower than the Ac3 point, ferrite is generated. Dislocations in this ferrite are reduced by annealing, and there are no dislocations that serve as a diffusion path for B (boron) during the second annealing, making it difficult to uniformly segregate boron. In addition, if the temperature is raised excessively, the austenite grain size will become larger than 10 μm. Therefore, the first heating temperature is set to the Ac3 point or higher. The first heating temperature is preferably the Ac3 point + 10°C or higher, and more preferably the Ac3 point + 15°C or higher. Since the austenite structure formed in the second annealing has the same crystal structure as the austenite structure formed in the first annealing, the first heating temperature is preferably 980° C. or less so that the austenite grain size in the first annealing is 10 μm or less. The first heating temperature is more preferably 950° C. or less. The Ac3 point is calculated using the following formula. Ac3(℃)=881-206×[%C]+53×[%Si]-15×[%Mn]-27×[%Cu]-20×[%Ni]-1×[%Cr]+41×[%Mo] (In the above formula, [%M] is the content (mass%) of element M in the steel sheet, and the value of an element that is not contained is 0 (zero).)
[0069] [Cooling process: Start cooling from the first heating temperature, and cool at an average cooling rate of 50°C / s or more until the cooling stop temperature is 100°C or higher but less than the Ms point] [Reheating process: Heat to a reheating temperature of 300°C to 400°C, hold at the reheating temperature for 60 seconds or more, and then cool to room temperature] After the first annealing step, in order to obtain a structure in which residual austenite exists at the prior austenite grain boundaries, the cold-rolled sheet is subjected to partial quenching and partitioning treatment in the cooling step. If the cooling stop temperature of the partial quenching is less than 100°C, martensite transformation occurs before C partitioning occurs, and a sufficient amount of residual austenite cannot be obtained before the second annealing. If the amount of residual austenite is insufficient, austenite with a different orientation from that in the first annealing is generated, and it is difficult to uniformly segregate B (boron) at the grain boundaries of such austenite. Therefore, the cooling stop temperature in the cooling step is 100°C or higher. The cooling stop temperature is preferably 120°C or higher, more preferably 150°C or higher. On the other hand, if the cooling end temperature is above the Ms point, martensitic transformation does not occur, so carbon distribution does not occur during the subsequent reheating, and retained austenite does not form before the second annealing. If the amount of retained austenite is insufficient, austenite with a different orientation from that in the first annealing is formed, and it is difficult to uniformly segregate B (boron) at the grain boundaries of such austenite. Therefore, the cooling stop temperature in the cooling step is set to be lower than the Ms point, preferably Ms point -10°C or lower, more preferably Ms point -20°C or lower. The Ms point is calculated using the following formula. Ms(℃)=499-308×[C]-10.8×[Si]-32.4×[Mn]-16.2×[Ni]-27×[Cr]-10.8×[Mo] (In the above formula, [M] is the content (mass%) of element M in the steel sheet, and the value of an element that is not contained is 0 (zero).)
[0070] If the average cooling rate is less than 50°C / s, ferrite transformation occurs. Since this ferrite contains almost no dislocations, this ferrite transformation slows down the diffusion of boron during the second annealing, and boron concentration at grain boundaries in the final structure becomes insufficient. Therefore, the average cooling rate is set to 50°C / s or more. The average cooling rate is preferably 60°C / s or more, and more preferably 70°C / s or more. The upper limit of the average cooling rate is not particularly limited, but if the cooling rate is too high, it becomes difficult to control the first cooling stop temperature, so the average cooling rate is preferably 1000°C / s or less, and more preferably 200°C / s or less. The average cooling rate (°C / s) in the cooling step is "(first heating temperature (°C))-(cooling stop temperature (°C)) / (cooling time (seconds) from the first heating temperature (°C) to the cooling stop temperature (°C))".
[0071] If the reheating temperature is less than 300°C, carbon distribution is insufficient, and retained austenite is not formed before the second annealing. If the amount of retained austenite is insufficient, austenite with a different orientation from that in the first annealing is formed, and it is difficult to uniformly segregate B (boron) at the grain boundaries of such austenite. Therefore, the reheating temperature is set to 300° C. or higher. The reheating temperature is preferably 310° C. or higher, and more preferably 320° C. or higher. On the other hand, if the reheating temperature exceeds 400°C, the untransformed austenite decomposes into cementite, and no residual austenite is formed before the second annealing. If the amount of residual austenite is insufficient, austenite with a different orientation from that in the first annealing is formed, and it is difficult to uniformly segregate B (boron) at the grain boundaries of such austenite. Therefore, the reheating temperature is set to 400°C or less. The reheating temperature is preferably 390°C or less, and more preferably 380°C or less.
[0072] Furthermore, if the holding time at the reheating temperature (reheating holding time) is less than 60 seconds, carbon distribution is insufficient and retained austenite is not generated before the second annealing. If the amount of retained austenite is insufficient, austenite with a different orientation from that in the first annealing is generated, and it is difficult to uniformly segregate B (boron) at the grain boundaries of such austenite. Therefore, the holding time at the reheating temperature is set to 60 seconds or more, preferably 80 seconds or more, and more preferably 100 seconds or more. The holding time at the reheating temperature is preferably 900 seconds or less, and more preferably 600 seconds or less. After being held at the reheating temperature, the material is cooled to room temperature. Here, the room temperature at which the cooling is stopped in the reheating step is not particularly limited, but may be 5 to 50°C.
[0073] [Sub-zero treatment process] Sub-zero treatment transforms the blocky retained austenite to obtain martensite with a high C concentration. From this martensite, new austenite with a different orientation than the first treatment is nucleated, resulting in grain boundaries with a non-uniform B concentration. Film-like retained austenite remains even after this treatment, and subsequent annealing forms an austenite structure with the same crystal orientation as the first austenite, with the grain boundaries becoming enriched and uniform in B. Although the specific conditions for the sub-zero treatment are not particularly limited, it is preferable to immerse the cold-rolled sheet after the reheating step in liquid nitrogen (-196°C) for 30 minutes or more. It is also preferable to immerse the cold-rolled sheet in liquid nitrogen for 3 hours or less.
[0074] [Second annealing process: Heat to a second heating temperature of Ac3 or higher] In the second annealing step, the steel sheet (cold-rolled sheet) obtained as described above is heated again to a second heating temperature of the Ac3 point or higher and annealed. During this process, austenite with the same orientation as the austenite generated in the first annealing is generated with the film-like retained austenite as the nucleus. During the generation process, B (boron) dissolved through dislocations in martensite before austenite transformation diffuses rapidly to the austenite grain boundaries, resulting in uniform boron segregation. If the second heating temperature is below the Ac3 point, ferrite is generated and the strength decreases. Therefore, the second heating temperature is set to the Ac3 point or higher. The second heating temperature is preferably the Ac3 point + 10°C or higher, more preferably the Ac3 point + 15°C or higher. On the other hand, if the temperature is increased too much, the austenite grain size becomes larger than 10 μm, and the delayed fracture properties deteriorate, so the second heating temperature is preferably 980° C. or less, and more preferably 950° C. or less.
[0075] [Plating process, alloying process] After the second annealing step, a plating step is performed in which at least one side of the steel sheet is plated to obtain a plated steel sheet. After the plating step, a heat treatment may be performed on the plated steel sheet (high-strength plated steel sheet) to alloy the plating layer of the plated steel sheet to obtain an alloyed plated steel sheet. The production conditions other than those mentioned above can be the same as those in the ordinary methods.
[0076] The plated steel sheet according to this embodiment obtained as described above preferably has a thickness of 0.5 mm or more, and more preferably has a thickness of 2.0 mm or less.
[0077] [Part] In this embodiment, a member can be provided that is at least partially made of the above-mentioned plated steel sheet. In one example, the above-mentioned plated steel sheet can be formed into a desired shape by press working to form an automobile part. The automobile part may contain a steel sheet other than the plated steel sheet according to this embodiment as a material. According to this embodiment, a plated steel sheet having a TS of 1180 MPa or more and having excellent delayed fracture resistance and platability can be provided, so that a member having a TS of 1180 MPa or more and having both excellent delayed fracture resistance and platability can be provided. The steel sheet according to this embodiment can be suitably used as an automobile part that contributes to weight reduction of the vehicle body. The plated steel sheet according to this embodiment can be suitably used in general members used as automobile parts, particularly as frame structural parts or reinforcing parts.
[0078] The method for producing the above-mentioned member includes a step of subjecting the above-mentioned plated steel sheet to at least one of forming and joining to form the member. The forming process may be performed by a general processing method such as pressing, without any restrictions. The joining process may be performed by a general welding method such as spot welding or arc welding, riveting, or crimping, without any restrictions. EXAMPLES
[0079] A steel having the chemical composition shown in Table 1, with the balance being Fe and unavoidable impurities, was melted in a converter to obtain a steel slab. The obtained slab was reheated, hot-rolled, and coiled to obtain a hot-rolled coil (hot-rolled sheet). Next, the hot-rolled coil was pickled while being uncoiled, and cold-rolled to obtain a cold-rolled sheet. The thickness of the hot-rolled sheet was 3.0 mm, and the thickness of the cold-rolled sheet was 1.2 mm. Annealing (first annealing step, cooling step, reheating step, subzero treatment step, second annealing step) was performed in a continuous hot-dip galvanizing line under the conditions shown in Table 2 to obtain plated steel sheets (hot-dip galvanized steel sheet (GI), alloyed hot-dip galvanized steel sheet (GA)). The hot-dip galvanized steel sheet was immersed in a 460°C plating bath and was coated with 35 g / m2 of zinc per side. 2 The coating weight of the galvannealed steel sheet was 45 g / m2 per side. 2 After adjusting the coating weight, the alloying treatment was carried out by holding at 520°C for 40 seconds. Sub-zero treatment was performed on all steel sheets except for steel sheet No. 6, which was immersed in liquid nitrogen (-196°C) for 60 minutes.
[0080] [Table 1]
[0081] [Table 2]
[0082] The obtained steel sheets were evaluated according to the above-mentioned methods for the total area ratio of martensite and bainite, the area ratio of retained austenite, the area ratio of ferrite, the prior austenite grain size, the B concentration of the prior austenite grain boundary between adjacent martensites, and the variation of the B concentration of the prior austenite grain boundary at the same grain boundary (the variation of the B concentration of the prior austenite grain boundary between adjacent martensites at the same grain boundary, and the variation of the B concentration of the prior austenite grain boundary between martensite and ferrite at the same grain boundary). In addition, the tensile strength and delayed fracture resistance were evaluated according to the methods described later. The results are shown in Table 3.
[0083] [Tensile test] The obtained steel sheets were subjected to a tensile test in accordance with JIS Z 2241 (2011). JIS No. 5 tensile test pieces were taken with the longitudinal direction perpendicular to the rolling direction, and a tensile test was performed to measure the tensile strength (TS). If the tensile strength TS was 1180 MPa or more, the tensile strength was judged to be good.
[0084] [Delayed fracture test] The delayed fracture resistance of the steel plate was evaluated as follows. A 30 mm x 110 mm test piece was taken from the obtained steel plate, with the rolling direction as the longitudinal direction. A strain gauge was attached to this test piece, and it was bent at 90 degrees V with a curvature radius of 7 mmR (R / t = 5.0). The opposing plate surfaces were pressed together, and the tensile stress of the test piece surface was set to 1800 MPa to prepare a test piece for evaluating delayed fracture resistance. This test piece for evaluating delayed fracture resistance was immersed in a hydrochloric acid solution of pH 3, and the occurrence of cracks after 100 hours was examined. Steel plates that did not develop cracks after 100 hours were judged to have good resistance to delayed fracture. In the table, steel plates that did not develop cracks after 100 hours were rated as "excellent" in resistance to delayed fracture, and other steel plates were rated as "poor" in resistance to delayed fracture.
[0085] [Plating evaluation] Regarding platability, each plated steel sheet was visually observed for the presence or absence of unplated areas, and those without unplated areas were deemed to have good platability. In the table, steel sheets that were deemed to have good platability are indicated as "excellent," and steel sheets that were deemed to have poor platability are indicated as "poor."
[0086] [Table 3]
[0087] As can be seen from Table 3, the examples of the present invention have a tensile strength TS of 1180 MPa or more, and are excellent in delayed fracture resistance and platability, while the comparative examples are inferior in at least one of tensile strength TS, delayed fracture resistance, and platability.
[0088] In addition, it was found that the steel sheets of the present invention were used to produce members obtained by forming, members obtained by joining, and members obtained by further forming and joining, and because the steel sheets of the present invention have high strength and excellent delayed fracture resistance and platability, they have the same high strength and excellent delayed fracture resistance and platability as the steel sheets of the present invention.
Claims
1. In mass percent, C: 0.10% or more and 0.30% or less, Si: more than 1.20% and less than 2.00%, Mn: 2.5% or more and 4.0% or less, P: 0.050% or less, S: 0.020% or less, Al: 0.10% or less, N: 0.01% or less, Ti: 0.100% or less, Nb: 0.002% or more and 0.050% or less, and B: 0.0008% or more and less than 0.0015% and has a composition satisfying the following formula (1), with the balance being Fe and unavoidable impurities: The sum of the area ratios of martensite and bainite is 95.0% or more, The area ratio of retained austenite is 4.8% or less, The area ratio of ferrite is 0.2% or more and 3.0% or less, The prior austenite grain size is 10 μm or less, The B concentration of the prior austenite grain boundaries between adjacent martensites is 0.05% or more by mass%, The variation in B concentration in the prior austenite grain boundary between adjacent martensite grains is less than 0.010% by mass%, A steel plate in which the variation in B concentration in a prior austenite grain boundary present between martensite and ferrite is 0.010% or more in mass percent within the same grain boundary; and a plating layer formed on at least one surface of the steel sheet. ([%N] / 14) / ([%Ti] / 47.9)<1.0...Formula (1) In formula (1), [%N] and [%Ti] respectively represent the N and Ti contents (mass%) in the steel.
2. The composition further includes, in mass%, V: 0.100% or less, Mo: 0.500% or less, Cr: 1.00% or less, Cu: 1.00% or less, Ni: 0.50% or less, Sb: 0.200% or less, Sn: 0.200% or less, Ta: 0.200% or less, W: 0.400% or less, Zr: 0.0200% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Co: 0.020% or less, REM: 0.0200% or less, Te: 0.020% or less, Hf: 0.10% or less, and Bi: 0.200% or less The plated steel sheet according to claim 1 , comprising at least one selected from the following:
3. A member made using the plated steel sheet according to claim 1 or 2.
4. A hot rolling process in which a steel slab having the composition according to claim 1 or 2 is hot rolled to obtain a hot rolled sheet; A pickling process for pickling the hot-rolled sheet; A cold rolling process in which the hot-rolled sheet after the pickling process is cold-rolled to obtain a cold-rolled sheet; A first annealing step of heating the cold-rolled sheet to a first heating temperature of Ac3 point or higher; A cooling step in which cooling is started from the first heating temperature to a cooling stop temperature of 100 ° C. or higher and lower than the Ms point at an average cooling rate of 50 ° C. / s or higher for the cold-rolled sheet after the first annealing step; After the cooling step, a reheating step of heating to a reheating temperature of 300° C. or more and 400° C. or less, holding the reheating temperature for 60 s or more, and cooling to room temperature; a sub-zero treatment step of performing sub-zero treatment after the reheating step; A second annealing step in which the steel sheet is obtained by heating the steel sheet to a second heating temperature of Ac3 or higher after the sub-zero treatment step; A plating step of subjecting the steel sheet to a plating treatment to obtain a plated steel sheet, A method for manufacturing a plated steel sheet, comprising: a steel sheet having a sum of an area ratio of martensite and bainite of 95.0% or more, an area ratio of retained austenite of 4.8% or less, an area ratio of ferrite of 0.2% to 3.0%, a prior austenite grain size of 10 μm or less, a prior austenite grain boundary between adjacent martensite particles having a B concentration of 0.05% or more by mass, a variation in the B concentration of the prior austenite grain boundary between adjacent martensite particles within the same grain boundary of less than 0.010% by mass, and a variation in the B concentration of the prior austenite grain boundary between martensite and ferrite within the same grain boundary of 0.010% by mass or more, and a plating layer formed on at least one surface of the steel sheet.
5. The method for producing a plated steel sheet according to claim 4, further comprising, after the plating step, an alloying step of subjecting the plated steel sheet to an alloying treatment.
6. A method for producing a component, comprising the step of subjecting the plated steel sheet according to claim 1 or 2 to at least one of forming and joining to produce a component.
Citation Information
Patent Citations
High strength cold rolled steel sheet excellent in workability and its production method
JP2008106351A
High yield ratio and high strength steel sheet excellent in workability
JP2013147736A
High formability super strength cold-roll steel sheet or steel strip, and manufacturing method therefor
US20170298466A1
Hot-dip zinc-coated steel sheet and method for manufacturing same
WO2020162561A1
Steel sheet, member, method for producing said steel sheet, and method for producing said member
WO2023008003A1